Progress of electrospun fibers as nerve conduits for neural tissue repair. (August 2014) - Mu, Ying; Wu, Fei; Lu, Yingrong; Wei, Liangming; Yuan, Weien
Nerve tissue regeneration approaches have gained much attention in recent years, and nerve conduits (NCs), which facilitate nerve tissue regeneration, have become an attractive alternative to nerve autologous graft. Several methods are proposed to fabricate NCs, including electrospinning, which is a widely used approach for NCs and other tissue scaffolds, and has advantages such as the ability to control the thickness, diameter and porosity of fibers, as well as its simple experimental set up. This article gives an overview of electrospun fibers for nerve conduits utilized in peripheral and central nerve regeneration. Natural and synthetic materials with different mechanical strength, degradation rates and biocompatibility are proposed. Several bioactive proteins that can help the process of nerve regeneration are introduced. Finally, some approaches to control the morphology of electrospun fibers and to deliver bioactive proteins are discussed in detail.